2014
DOI: 10.1177/0018720814526617
|View full text |Cite
|
Sign up to set email alerts
|

Use of EEG Workload Indices for Diagnostic Monitoring of Vigilance Decrement

Abstract: Lower-frequency alpha may be used to diagnose loss of operator alertness on tasks requiring vigilance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(91 citation statements)
references
References 49 publications
5
83
2
1
Order By: Relevance
“…For descriptors, the max descriptor was the most frequent. For frequency bands, the frequencies between 4-16Hz (i.e., theta, alpha, low-beta) were more relevant to workload estimation, and these findings aligned with results reported in References [54,92]. Although our results aligned with many current studies, other studies reported relationships between EEG and workload that were not observed in the current study.…”
Section: A Closer Examination Of Eeg Featuressupporting
confidence: 91%
“…For descriptors, the max descriptor was the most frequent. For frequency bands, the frequencies between 4-16Hz (i.e., theta, alpha, low-beta) were more relevant to workload estimation, and these findings aligned with results reported in References [54,92]. Although our results aligned with many current studies, other studies reported relationships between EEG and workload that were not observed in the current study.…”
Section: A Closer Examination Of Eeg Featuressupporting
confidence: 91%
“…This processing generated an increase in mental activity, and a high perceptual process load can impair the ability to detect stimuli in environments that overload the working memory 24 . It might worsen attention and concentration, resulting in a decrease in vigilance and an increase in mental effort when associated with another low frequency, such as alpha 25 , and this may partly explain our findings. Another important finding was that we did not find a significant difference between the rest conditions and meditation at the prefrontal derivations (Fp1, Fp2) in the MG.…”
mentioning
confidence: 76%
“…Current vigilance research suggests that hemodynamic indices of frontal brain metabolism such as CBFV (Warm et al, 2012) and EEG measures (Kamzanova, Kustubayeva, & Matthews, 2014) may be more diagnostic of vigilance than traditional autononic arousal measures.…”
Section: Discussionmentioning
confidence: 99%